Paperja : Organisasi Perantau Jawa di Bukittinggi-Agam (1980-2025) - Meilinda Sri Wahyuni; Najmi Najmi (Jurusan Sejarah FIS UNP, 2026)
This study examines the development of the Javanese migrant organization, Paguyuban Perantau Jawa (PAPERJA), in the city of Bukittinggi and Agam Regency from 1980 to 2025. The study aims to explain the background of PAPERJA’s formation and its development during that period. The research method employed is the historical method, which consists of four stages: heuristics, source criticism, interpretation, and historiography. During the heuristic stage, data were collected through interviews, archives, documentation, and membership records. The source criticism stage was conducted to assess the validity of the obtained sources. The interpretation stage was used to analyze and connect historical facts chronologically, while the historiography stage involved the systematic writing of the research findings. The results indicate that PAPERJA was formed as a unifying platform for Javanese migrants and experienced significant development through 2025. This development was marked by leadership transitions, an increase in membership, the expansion of the organization’s territory, and the growth of social activities such as disaster relief, community celebrations, religious study groups, the management of communal graves, and the establishment of cooperatives. PAPERJA plays a vital role in strengthening solidarity and a sense of community among the Javanese migrant community in Bukittinggi City and Agam Regency.